2018
DOI: 10.3389/fpls.2018.00363
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous Applications of Brassinosteroids Improve Color of Red Table Grape (Vitis vinifera L. Cv. “Redglobe”) Berries

Abstract: Color and other quality parameters of “Redglobe” grape (Vitis vinifera L.) berries were evaluated after treatment with brassinosteroid (BR) analogs. Three BRs analogs (24-epibrassinolide, Triol, or Lactone) were applied at three concentrations (0.0, 0.4, or 0.8 mg⋅L-1), at the onset of veraison. A commercial formulation (B-2000®) was also applied, at a recommended rate of 0.06 mg⋅L-1. The tested BR analogs were effective improving berry color (evaluated as color index for red grapes, CIRG), increasing the leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 36 publications
4
14
0
Order By: Relevance
“…These increases coincided with the upregulation of transcription levels of VvCWIN , VvHT3 , 4 , 5 , 6 , and VvSUC12 , 27 during véraison ( Xu et al, 2015 ). Vergara et al (2018) also found that BR analogs increased soluble solids and anthocyanins in ‘Redglobe’ grapes. Together, these data suggested that BR positively controls sugar accumulation in grapes during véraison.…”
Section: The Effect Of Hormone On Sink Strengthmentioning
confidence: 83%
“…These increases coincided with the upregulation of transcription levels of VvCWIN , VvHT3 , 4 , 5 , 6 , and VvSUC12 , 27 during véraison ( Xu et al, 2015 ). Vergara et al (2018) also found that BR analogs increased soluble solids and anthocyanins in ‘Redglobe’ grapes. Together, these data suggested that BR positively controls sugar accumulation in grapes during véraison.…”
Section: The Effect Of Hormone On Sink Strengthmentioning
confidence: 83%
“…These results are in line with a study of the effect of exogenous application of EBL on Basmati rice submitted to salinity stress [ 64 ]. Besides, analog 1, which is the more efficient exogenous anti-stress molecule used in this work, has also demonstrated interesting effects when is applied to grapes and berries, i.e., increasing of index color values by increasing the content of soluble solids and dehydroxylated anthocyanins [ 65 ]. Thus, exogenous application of BRs analogs is a promising tool for enhancement of growth and stress tolerance in plants.…”
Section: Resultsmentioning
confidence: 99%
“…Exogenous application of growth regulators is an important tool for improving quality parameters of grape berries, including size, sensory characteristics and colour, among others (El-Kereamy et al 2003, Han and Lee 2004, Jeong et al 2004, Symons et al 2006, Fanzone et al 2010, González et al 2012. Although BRs are a group of hormones that participate in the ripening of grape berries (Symons et al 2006, Xu et al 2015, Vergara et al 2018, their use as a plant growth regulator in tablegrape production has not been widely studied.…”
Section: Discussionmentioning
confidence: 99%